Bioactive Sol–Gel Glasses at the Atomic Scale: The Complementary Use of Advanced Probe and Computer Modeling Methods. (15th April 2016) - Christie, Jamieson K.; Cormack, Alastair N.; Hanna, John V.; Martin, Richard A.; Newport, Robert J.; Pickup, David M.; Smith, Mark E.
Abstract : Sol–gel‐synthesized bioactive glasses may be formed via a hydrolysis condensation reaction, silica being introduced in the form of tetraethyl orthosilicate (TEOS), and calcium is typically added in the form of calcium nitrate. The synthesis reaction proceeds in an aqueous environment; the resultant gel is dried, before stabilization by heat treatment. These materials, being amorphous, are complex at the level of their atomic‐scale structure, but their bulk properties may only be properly understood on the basis of that structural insight. Thus, a full understanding of their structure‐property relationship may only be achieved through the application of a coherent suite of leading‐edge experimental probes, coupled with the cogent use of advanced computer simulation methods. Using as an exemplar a calcia–silica sol–gel glass of the kind developed by Larry Hench, in the memory of whom this paper is dedicated, we illustrate the successful use of high‐energy X‐ray and neutron scattering (diffraction) methods, magic‐angle spinning solid‐state NMR, and molecular dynamics simulation as components to a powerful methodology for the study of amorphous materials.